Legal framework of reconciliation process under Malaysian Islamic Family Law: A proposal for reform - Abdul Hak, Nora; Mohd Zin, Najibah; Sowell, Sarafuddin Abdul Syahid (2017)
Under the Malaysian Islamic Family law, reconciliation process for Muslim marriages is clearly stated in two different provisions; one, which is conducted by the reconciliatory committee and the other, is by the appointment of arbitration proceedings (tahkim) in the court. When divorce application is disputed by one of the parties or when the Shariah court believes that there is possibility of reconciliation, the court shall appoint a conciliatory committee to reconcile the Muslim couple. The conciliatory committee consist of a religious officer and two other persons, one to act for the husband and the other to act for the wife. The two other persons appointed may be close relatives of the couples having knowledge of the circumstances of the case taking into account the role of extended family support during the reconciliation effort. If the couple could not be reconciled, the court may refer the matter to arbitration proceedings with an authorisation to divorce the couple should the effort is not successful. Reconciliation platform is a positive effort towards assisting the couple to preserve their marriage life. However, the question is how far the reconciliation process as provided by the law brings success towards achieving its goal to preserve marriage. With the high number of divorce rate steadily increased every year, it is reasonable to suggest that the reconciliatory law does not effectively save Muslim marriages. A few states have improved the reconciliation process by appointing arbitrators as officers of the court who are non-family members to serve in the arbitration proceedings, however, from a random survey that has been conducted with appointed arbitrators, there is no significant improvement in reducing the number of divorce. This is due to the fact that most couple who were attending reconciliation process believed that the marriage is over once the application for divorce is registered. Therefore this paper will analyse legal problems associated with the application of a reconciliatory process and to suggest for an effective system to the extent of institutionalising arbitration proceedings within the Shariah court system. The study adopts qualitative analysis employing both library research, and interviews with selected respondents.